STPM physics (5-year series STPM, 2004)
Pearson Longman's 5-year series bring together, for the first time, a collection of past-year papers and specimen answers to help Pre-U students prepare for the STPM and MUET examinations. The specimen answers provided serve to guide students in their quest to excel in the papers they undertake.